Oxamate salts as novel agents for the restoration of marble and limestone substrates: case study of ammonium N-phenyloxamate. (28th January 2016) - Maiore, Laura; Aragoni, M. Carla; Carcangiu, Gianfranco; Cocco, Ombretta; Isaia, Francesco; Lippolis, Vito; Meloni, Paola; Murru, Arianna; Slawin, Alexandra M. Z.; Tuveri, Enrica; Woollins, J. Derek; Arca, Massimiliano
Abstract : The treatment of calcareous stone substrates, such as weathered marble and biomicritic limestone, with ammonium N -phenyloxamate results in the deposition of the corresponding monohydrated calcium salt. Abstract : The ammonium salt of N -phenyloxamic acid (AmPhOxam) was synthesised, characterised by FT-IR, FT-Raman, UV-Vis, 1 H-NMR spectroscopic methods and single crystal X-ray diffraction, and evaluated as a protective and consolidating agent for calcareous stone substrates under mild conditions. Hydro-alcoholic solutions of AmPhOxam were tested for the treatment of naturally weathered white marble and biomicritic limestone. Mercury intrusion porosimetry, FT-NIR spectroscopy measurements and SEM microscopy showed the formation of a superficial protective layer of crystals of the corresponding monohydrated calcium salt, CaPhOxam, on both treated stones.